EFEKTIVITAS PSIKOEDUKASI KETERAMPILAN SOSIAL UNTUK MENURUNKAN KECEMASAN SOSIAL PADA REMAJA TUNARUNGU - Agustin, Ardianti (Esa Unggul University, 2019)
This study aims to reduce social anxiety in deaf adolescents through psychoeducation of social skills. The research design used was quasi experiment Oneqroup Pretest-Posttest design with psychoeducation intervention of social skills. Sample of this research was 6 (six) students selected by purposive sampling technique through observation stage and direct interview both to student and teacher of class which was in SMA Karya Mulia Surabaya. The collected data was analyzed by using mannwhitneytest and the result was Z = - 2,741 with significance level 0,006 it means significant social anxiety score before and after psychoeducation of social skill. Based on the results of the study concluded that psychoeducation of social skills effectively reduce social anxiety in deaf adolescentsKeywords : social skill, social anxiety, deaf adolescent